Fine structure and histochemistry of epithelioid cells in sarcoidosis - James, E. M. Valerie (1974)
James, E. M. Valerie and Jones Williams, W. (1974).Thorax, 29, 115-120. Fine structure and histochemistry of epithelioid cells in sarcoidosis. In this fine structure study of epithelioid cells in the granulomata of sarcoidosis we confirm our previous findings that they appear to be synthesizing rather than phagocytosing cells. The numerous characteristic intracytoplasmic vesicles, 0·5 μ in size, are shown to contain mucoglycoprotein and only rarely acid phosphatase activity. Epithelioid cells show varying quantities of extravesicular acid phosphatase activity which is sometimes on the outer surface of the protein-containing vesicles. The possible role of secretory products of epithelioid cells in the formation and persistence of granulomata is discussed. It is suggested that epithelioid cells may be forming lymphokines.